101 textures in graphite & charcoal - Pearce, Steven (Lake Forest, CA : Walter Foster, 2017)
101 Textures in Graphite & Charcoal provides artists with step-by-step instructions for learning how to draw a wide variety of the most common textures and surfaces.
Master record variable field(s) change: 072
Keywords: Charcoal drawing -- Technique; Pencil drawing -- Technique; ART -- Techniques -- Drawing; Charcoal drawing -- Technique; Pencil drawing -- Technique; Electronic books